Kebijakan Kepemilikan Rumah Susun di Indonesia - Febriani, Ayu Fitria (University of Jember, 2019)
In the concept of agrarian law, it is not something new anymore that the land is getting less and less while the human need for land increasingly day increases. This is what makes the government then make a policy in the construction of housing in the form of horizontally building homes to save land called flats. The development of the flats is expected to meet the needs of the community will be a place to live and can improve the quality of life of the community. but over time, in perkembangnnya development of flats is also not free from various problems. This article examines the legal certainty of the ownership status of apartment units, not only from the land ownership aspect in which the high rise is built, but also includes the initial publication of the master certificate issued on behalf of the developer for the first time. Developers as business actors in trust by the government to get the first certificate of a development of flats, this often affects the inhabitants of apartment units. Although each resident of a flats unit may own / hold property certificates of units from separate flats between joint and individual sections, sometimes ownership status with a title certificate also can not protect the inhabitants of various disputes. Therefore, to minimize the occurrence of disputes, legal certainty becomes important to protect the parties concerned so as not to harm each other. Legal protection in such cases can be done by means of preventive law protection and repressive law protection.